Impacts of Agricultural Policies on Structural and Technological Changes in Agricultural Holdings: The Case of the European Union - Martinho, Vítor (2022)
The Common Agricultural Policy (CAP) experienced several reforms since the beginning of the European Economic Community (EEC) in the fifties/sixties to deal with the evolution of the realities and to adjust to the adherence of new Member States over the years. If the Great Reform of 1992 promoted important changes in the CAP instruments and measures, the CAP reform of 2003 do not brought fewer transformations with the decoupling of the subsidies from production and activities and the creation of the single farm payment scheme. These reforms had relevant impacts on the European Union (EU) farms. The main objective of this chapter is to assess the impacts of the CAP reforms of 2003, 2009 (“Health Check”) and 2013 on the structural and technological dimensions of the EU farms. For that statistical information from the Farm Accountancy Data Network (FADN) was considered for the periods 2004–2006 and 2018–2020. These data were assessed through statistical approaches. As main insights, it is worth highlighting the impacts of the CAP reforms on the decisions of the farmers, to take advantage of the new policy instruments, and on attracting new farmers with subsequent implications on the structural and technological dimensions.